THE EFFECT OF APUS BAMBOO (Gigantochloa apus) LEAVES INFUSION TO MORTALITY RATE AND MORPHOMETRY OF Haemonchus contortus ADULT WORM IN VITRO - Budi Purwo Widiarso; Wisnu Nurcahyo; Kurniasih Kurniasih; Joko Prastowo (Jurnal Kedokteran Hewan, 2017)
This present project was carried out to determine the effect of apus bamboo (Gigantochloaapus )leaves infusion to mortality rate and morphometry of Haemonchus contortus adult worms in vitro. The formulated tools were collected through camera, 3 ml syringe, object glass, deck glass, mortar, drip dropper, waterbath, microscope, stopwatch, counter check, oven, erlenmeyer flask, electric scale, surgical scissor, and pipette. The allocated materials used in this studywere bamboo leaves infusion, Haemonchus contortus adult worms, aquadestilata, ethanol and NaCl 0.62%. The research was firstly concernedwith making 0.1% and 1% apus bamboo leaves infusion. The samples were obtained from Haemonchus contortus collection. Adult worms were obtained directly from abomasum of naturally infected goats that were cut at Animal Slaughter House (RPH). To investigate the matter, mortality rates of adult worms at various doses and times of observation as well as differences in Haemonchus contortus morphometry were analyzed using ANOVA. The findings disclosed that apus bamboo leaves infusion demonstrated a significant difference in the mortality rate of adult worms Haemonchus contortusat various doses and times of observation. This report presented the findings of research that the best dose to increase the mortality of worms was 1% bamboo leaves infusion. Moreover, apus bamboo leaves infusion affected the morphometry of Haemonchus contortus adult worms, especially in body length, cervical papilla width, and spicules length in males, and body length, cervical papilla width, and vulvar length in females.